Commodity Booms and Government Expenditure Responses - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 1991)
This paper develops a model incorporating asymmetric government expenditure behavior in response to a windfall revenue gain occasioned by a transitory commodity boom. The model is used to illustrate the transitional dynamics of a stylized economy during the boom period and the nature of the macroeconomic disequilibria which emerge in the post-boom period. Country case studies of Sri Lanka, Malaysia, and Kenya support the model's predictions and the protracted nature of adjustment following the waning of the boom.